Does active application of universal adhesives to enamel in self-etch mode improve their performance?. Issue 9 (September 2015) - Loguercio, Alessandro D.; Muñoz, Miguel Angel; Luque-Martinez, Issis; Hass, Viviane; Reis, Alessandra; Perdigão, Jorge
Abstract Objectives To evaluate the effect of adhesion strategy on the enamel microshear bond strengths (μSBS), etching pattern, and in situ degree of conversion (DC) of seven universal adhesives. Methods 84 extracted third molars were sectioned in four parts (buccal, lingual, proximal) and divided into 21 groups, according to the combination of the main factors adhesive (AdheSE Universal [ADU], All-Bond Universal [ABU], Clearfil Universal [CFU], Futurabond U [FBU], G-Bond Plus [GBP], Prime&Bond Elect (PBE), and Scotchbond Universal Adhesive [SBU]), and adhesion strategy (etch-and-rinse, active self-etch, and passive self-etch). Specimens were stored in water (37 °C/24 h) and tested at 1.0 mm/min (μSBS). Enamel–resin interfaces were evaluated for DC using micro-Raman spectroscopy. The enamel-etching pattern was evaluated under a field-emission scanning electron microscope (direct and replica techniques). Data were analyzed with two-way ANOVA and Tukey's test (α = 0.05). Results Active self-etch application increased μSBS and DC for five out of the seven universal adhesives when compared to passive application (p < 0.001). A deeper enamel-etching pattern was observed for all universal adhesives in the etch-and-rinse strategy. A slight improvement in etching ability was observed in active self-etch application compared to that of passive self-etch application. Replicas of GBP and PBE applied in active self-etch mode displayed morphological features compatible with water droplets. The DC of GBP and PBE were not affected by the application/strategy mode. Conclusions In light of the improved performance of universal adhesives when applied actively in SE mode, selective enamel etching with phosphoric acid may not be crucial for their adhesion to enamel. Clinical significance The active application of universal adhesives in self-etch mode may be a practical alternative to enamel etching in specific clinical situations.